Ten-year follow-up of infliximab treatment for uveitis in Behçet disease patients: A multicenter retrospective study - Takeuchi, Masaru; Usui, Yoshihiko; Namba, Kenichi; Keino, Hiroshi; Takeuchi, Masaki; Takase, Hiroshi; Kamoi, Koju; Hase, Keitaro; Ito, Takako; Nakai, Kei; Maruyama, Kazuichi; Kobayashi, Eri; et al. (Frontiers in Medicine, 2023)
Purpose To evaluate 10-year outcome of infliximab (IFX) treatment for uveitis in Behçet disease (BD) patients using a standardized follow-up protocol. Design Retrospective longitudinal cohort study. Participants 140 BD uveitis patients treated with IFX enrolled in our previous study. Methods Medical records were reviewed for demographic information, duration of IFX treatment, number of ocular attacks before IFX initiation, best corrected visual acuity (VA) at baseline and 1, 2, 3, 4, 5, and 10 years after IFX initiation, uveitis recurrence after IFX initiation and main anatomical site, concomitant therapies, and adverse events (AEs). Main outcome measures 10-year IFX continuation rate and change in LogMAR VA. Results Of 140 BD patients, 106 (75.7%) continued IFX treatment for 10 years. LogMAR VA improved gradually after initiation of IFX, and the improvement reached statistical significance from 2 years of treatment. Thereafter, significant improvement compared with baseline was maintained until 10 years, despite a slight deterioration of logMAR VA from 5 years. However, eyes with worse baseline decimal VA < 0.1 showed no significant improvement from baseline to 10 years. Uveitis recurred after IFX initiation in 50 patients (recurrence group) and did not recur in 56 (non-recurrence group). Ocular attacks/year before IFX initiation was significantly higher in the recurrence group (2.82 ± 3.81) than in the non-recurrence group (1.84 ± 1.78). In the recurrence group, uveitis recurred within 1 year in 58% and within 2 years in 74%. Seventeen patients (34%) had recurrent anterior uveitis, 17 (34%) had posterior uveitis, and 16 (32%) had panuveitis, with no significant difference in VA outcome. In addition, logMAR VA at 10 years did not differ between the recurrence and non-recurrence groups. AEs occurred among 43 patients (30.7%), and 24 (17.1%) resulted in IFX discontinuation before 10 years. Conclusions Among BD patients with uveitis who initiated IFX, approximately 75% continued treatment for 10 years, and their VA improved significantly and was maintained for 10 years. Uveitis recurred in one-half of the patients, but visual acuity did not differ significantly from the patients without recurrence.